A Gold(III) Pincer Ligand Scaffold for the Synthesis of Binuclear and Bioconjugated Complexes: Synthesis and Anticancer Potential. Issue 14 (12th February 2018) - Bertrand, Benoît; O'Connell, Maria A.; Waller, Zoë A. E.; Bochmann, Manfred
Abstract: Cyclometalated (C^N^C)Au III complexes bearing functionalized N‐heterocyclic carbene (NHC) ligands provide a high‐yielding, modular route to bioconjugated and binuclear complexes. This methodology has been applied to the synthesis of bioconjugated complexes presenting biotin and 17α‐ethynylestradiol vectors, as well as to the synthesis of bimetallic Au III /Au I complexes. The in vitro antiproliferative activities of these compounds against various cancer cells lines depend on the linker length, with the longer linker being the most potent. The estradiol conjugateAuC6 Estra proved to be more toxic against the estrogen receptor positive (ER+) cancer cells than against the ER− cancer cells and non‐cancer cells. The bimetallic complexAuC6 Au was more selective for breast cancer cells with respect to a healthy cell standard than the monometallic complexAuNHC . The metal uptake study on cells expressing or not biotin and estrogen receptors revealed an improved and targeted delivery of gold for both the bioconjugated complexesAuC6 Biot andAuC6 Estra compared to the non‐vectorised analogueAuNHC . The investigations of the interaction of the bioconjugates and bimetallic complexes with human telomeric G‐quadruplex DNA using FRET‐melting techniques revealed a reduced ability to stabilize this DNA structure with respect to the non‐vectorised analogueAuNHC . Abstract : Gold(III) bioconjugates : Modification of pincer‐stabilized Au III NHC complexes gives bioconjugates and bimetallic complexes by a synthetically flexible method which enables the facile variation of the linker length and biovectors as well as the introduction of a second metal fragment. The compounds outline a possible strategy for improving selectivity in anti ‐cancer compounds.